Pengaruh Transparansi, Akuntabilitas, dan IGCG terhadap Tingkat Kepercayaan Muzakki di Lembaga Amil Zakat Dompet Amanah Umat - Ilyas Junjunan, Mochammad (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2020)
The purpose of this study was to determine the effect of transparency, accountability and Islamic good corporate governance on the level of trustworthiness muzakki in dompet amanah umat amil zakat institution, Sidoarjo Regency. The population of this research is all permanent muzakki in the DAU amil zakat institute of Sidoarjo Regency and 42 respondents who participated in the study. The research analysis technique used multiple linear regression with a significant level of 5% and used t-table testing. The results obtained indicate that transparency and the application of Islamic good corporate governance are able to significantly and positively influence the trust level of muzakki. Meanwhile, the accountability in this study is not significantly able to influence the level of trust of muzakki in the dompet amanah umat amil zakat institution of Sidoarjo Regency.